Cover Picture: Hexaphyrin as a Potential Theranostic Dye for Photothermal Therapy and 19F Magnetic Resonance Imaging (ChemBioChem 10/2017). (2nd May 2017) - Higashino, Tomohiro; Nakatsuji, Hirotaka; Fukuda, Ryosuke; Okamoto, Haruki; Imai, Hirohiko; Matsuda, Tetsuya; Tochio, Hidehito; Shirakawa, Masahiro; Tkachenko, Nikolai V.; Hashida, Mitsuru; Murakami, Tatsuya; Imahori, Hiroshi
Abstract : The cover picture shows a hexaphyrin as a potential theranostic expanded porphyrin for use in both sustained photothermal heat generation and 19 F magnetic resonance imaging (MRI). Expanded porphyrins have two potential key features suitable for theranostic agents, excellent absorption in the near infrared (NIR) region and the possibility of introducing multiple fluorine atoms at structurally nearly equivalent positions. Under NIR light, the hexaphyrin showed intense photothermal and weak photodynamic effects, which were most likely due to its low‐lying excited states close to that of singlet oxygen. This sustained photothermal effect caused the ablation of cancer cells more effectively than the photodynamic effect of indocyanine green, a clinically used dye. In addition, the hexaphyrin that has 12 trifluoromethyl groups showed potential for use in the visualization of tumors by 19 F MRI due to the presence of these multiple fluorine atoms. More information can be found in the full paper by T. Matsuda, M. Shirakawa, T. Murakami, H. Imahori et al. onpage 951 in Issue 10, 2017 (DOI:10.1002/cbic.201700071 ).